2009
DOI: 10.2989/ajar.2009.8.2.9.861
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to information and communication about HIV/AIDS and perceived credibility of information sources among young people in northern Tanzania

Abstract: Young people in sub-Saharan Africa constitute an important group for HIV prevention efforts. Determining their exposure to HIV/AIDS information and communication and their perceived credibility of information sources is imperative to the development of interventions. However, the majority of studies on this topic have been conducted among school-based populations, with few focused on those out of school or on comparing the two groups. A structured face-to-face interview was completed by 993 young people out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
(28 reference statements)
4
18
2
Order By: Relevance
“…In terms of religious affiliation, this was found to be a significant predictor of experiencing silence in one site in South Africa (Mankweng), with Catholics and other affiliations significantly more likely to report silence than Protestants [32]. Age was not found to be associated with communication about HIV/AIDS in one of the studies [38], but this was not consistent with others studies in the review. For instance, in the multi-site study, it was found that students who communicated about HIV and sex with parents were more likely to be older in Tanzania and one of the South African sites (Mankweng), while age was not associated with silence in the Cape Town site [32,33].…”
Section: Resultsmentioning
confidence: 85%
“…In terms of religious affiliation, this was found to be a significant predictor of experiencing silence in one site in South Africa (Mankweng), with Catholics and other affiliations significantly more likely to report silence than Protestants [32]. Age was not found to be associated with communication about HIV/AIDS in one of the studies [38], but this was not consistent with others studies in the review. For instance, in the multi-site study, it was found that students who communicated about HIV and sex with parents were more likely to be older in Tanzania and one of the South African sites (Mankweng), while age was not associated with silence in the Cape Town site [32,33].…”
Section: Resultsmentioning
confidence: 85%
“…It was found out that while most male adolescents, both in-school and out-of-school, prefer to talk to their friends, in-school and out-of-school females prefer to obtain this information from their mothers [23]. Other studies have also shown that between the two parents, the mother is the preferred party, when it comes to communication about sexuality for both male and female adolescents [24] [25].…”
Section: Young People's Perceptions On Caretaker-adolescent Communicamentioning
confidence: 99%
“…While some studies find parental sexual communication to be associated with a higher likelihood of abstinence [25,26], others find the reverse [27,28]. Many of the studies on sexual communication also focus on mothers [28][29][30][31], while paying less attention to the effect of communicating with fathers and friends. Although social support is lesscommonly examined, few studies have begun to examine the effect of cash transfers on adolescent and youth sexual behaviour [32,33].…”
Section: Introductionmentioning
confidence: 99%